Fiqh Discourse on Water: Integrating Social Capital and Mosque-Based Charity through Concurrent Triangulation - Hendra Darmawan; Aziz, Muhammad; Nurkholis (Fakultas Studi Islam dan Peradaban, Universitas Muhammadiyah Yogyakarta, 2025)
Since 2010, mosque revitalization has become a strategic priority of Muhammadiyah, emphasizing the integration of religious observance with community-based empowerment. This study examines the Garbage Charity Program (Sedekah Sampah) as a transformative model of mosque-led initiatives that promote belief, worship practices, and civic engagement. Grounded in Social Capital Theory, the research examines how trust, norms, and social networks are fostered through environmentally motivated religious actions. Utilizing a Concurrent Triangulation Design, qualitative data were collected through field observations, semi-structured interviews with stakeholders, and document analysis, enabling methodological cross-validation. The findings indicated that the program fosters mutual trust and collective responsibility among mosque congregants, while reinforcing Islamic ethical norms related to charity and environmental stewardship. The initiative has gained traction beyond Bantul, with its success replicated in Central and West Java, and it has been recognized both nationally and internationally. It has expanded to include eco-mosque features such as rainwater harvesting and greywater filtration for ablution, promoting sustainability through faith-based frameworks. This convergence of religious values and environmental consciousness generates robust spiritual and social capital. In conclusion, mosque-based empowerment initiatives can significantly contribute to community resilience and sustainable development when anchored in localized religious practices and supported by substantial social capital.